Analysis Semiotic of Meaning Courage in Qaṣīdah (al-Burdah, al- Niffarīyah, al-Mutanabbī, and al-Ahtyar) - Sarah, Sarah; Amelya, Asy Syifa Reza; Sopian, Asep; Pauzi, Miftah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This study aims to analyze the semiotic meaning of the word "courage" in four classical Arabic Qaṣīdahs: Qaṣīdah al-Burdah, Qaṣīdah al-Niffarīyah, Qaṣīdah al-Mutanabbī, and Qaṣīdah al-Ahtyar. This study uses Roland Barthes' semiotic theory to identify the signifiers, signs, and connotative meanings of the word "courage" in these poems. This research uses a qualitative-descriptive approach and a content analysis research design. The data collection techniques used are literature reviews. Primary data is in the Qaṣīdah al-Burdah, Qaṣīdah al-Niffarīyah, Qaṣīdah al-Mutanabbī, and Qaṣīdah al-Ahtyar. Secondary data comes from readings related to the study. The data obtained is reduced, displayed, and verified. The findings show that the semiotic analysis of the word "courage" in the four Qaṣīdahs reveals a testament to the enduring value of courage in guiding Muslims to face challenges and uphold their beliefs in a changing world. The findings of this study offer valuable insights into the rich and nuanced understanding of courage in Islamic culture. These insights can contribute to a deeper appreciation of the Islamic ethical framework and its relevance in contemporary society. In addition, the methodology of this study demonstrates the applicability of semiotic analysis in unearthing deeper meanings embedded in literary and cultural texts.